High-Grade Leiomyosarcoma Arising in a Previously Replanted Limb - Tiffany J. Pan; Liron Pantanowitz; Kurt R. Weiss (Case Reports in Oncological Medicine)
Sarcoma development has been associated with genetics, irradiation, viral infections, and immunodeficiency. Reports of sarcomas arising in the setting of prior trauma, as in burn scars or fracture sites, are rare. We report a case of a leiomyosarcoma arising in an arm that had previously been replanted at the level of the elbow joint following traumatic amputation when the patient was eight years old. He presented twenty-four years later with a 10.8 cm mass in the replanted arm located on the volar forearm. The tumor was completely resected and pathology examination showed a high-grade, subfascial spindle cell sarcoma diagnosed as a grade 3 leiomyosarcoma with stage pT2bNxMx. The patient underwent treatment with brachytherapy, reconstruction with a free flap, and subsequently chemotherapy. To the best of our knowledge, this is the first case report of leiomyosarcoma developing in a replanted extremity. Development of leiomyosarcoma in this case could be related to revascularization, scar formation, or chronic injury after replantation. The patient remains healthy without signs of recurrence at three-year follow-up.